Cambodia's Muslims and the Malay world: Malay language, Jawi script, and Islamic factionalism from the 19th century to the present - Bruckmayr, Philipp (Brill's Southeast Asian library, 2019)
Introduction: religious change and intra-Muslim factionalism -- 1. Foregrounding the jawization of Islam in Cambodia -- 2. On the eve of jawization and colonial rule -- 3. Chams and Malays in late pre-colonial and early colonial Cambodia -- 4. Observing structural and processual dispositions for jawization -- 5. Jawization in Cambodia's diverse Muslim landscape of the 1930s -- 6. Agents, nodes and vehicles of jawization -- 7. The French role in jawization and factionalism in Cambodian Islam -- 8. The legacies of jawization and anti-jawization -- Bibliography -- Index